LITERATURE AND THE ECOLOGICAL CRISIS: AN ECOCRITICAL STUDY OF THE NOVEL GEMURUH IN THE CONTEXT OF THE SINABUNG ERUPTION - Sumiati, Sumiati; Ramadhan, Zul Fitrah (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study applies Greg Garrard’s ecocritical framework to analyze Gemuruh, a novel by Hilmi Faiq that explores the complex relationship between humans and the environment in the context of the eruption of Mount Sinabung. Using six main aspects of ecocriticism, this study identifies how natural disasters are represented not only as destructive events, but also as triggers for personal transformation, community resilience, and ecological awareness. The analysis shows that volcanic ash and environmental degradation (pollution) are depicted alongside the cultural and emotional attachment of the Karo people to their land (settlements and wilderness). Apocalyptic imagery affirms the destructive power of nature as well as the ethical urgency of disaster preparedness, while representations of animals and the earth highlight interconnectedness within the ecological system. Through a combination of documentary-style narrative and lyrical prose, Gemuruh builds a layered reflection on the struggle for survival, loss, and coexistence with an unpredictable environment. This research contributes to the international ecocritical discourse by highlighting the Indonesian literary perspective on the environmental crisis and offering insights into the role of literature in fostering ecological empathy and disaster literacy.